2017
DOI: 10.1016/j.repbio.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive features and use of an anti-inflammatory drug in estrus-induced dairy goats artificially inseminated in a standing position with cervix immobilization

Abstract: This study evaluated reproductive features and role of Flunixin-Meglumine at timed artificial insemination (AI), using a new technique of standing position with cervix immobilization. In Experiment 1, 10 goats (n=5 nulliparous [Null] and 5 pluriparous [Plu]) were evaluated after estrus induction by recorded reproductive parameters to define the ideal time for AI. In Experiment 2, goats were artificially inseminated 51-54h after sponge removal with frozen-thawed semen. At AI, 1mL saline (CONTROL; 18 Null and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…In Experiment 2, eighty multiparous dairy goats with at least seven months of lactation (15 Alpine, 38 Saanen and 27 Toggenburg) were grouped by milk production, breed, BW, BCS and breeding methods, and then similarly allocated to one of the following gonadotropin treatments: pFSH (n = 26; BW: 45.1 ± 14.9 kg, BCS: 3.0 ± 0.4), eCG (n = 27; BW: 45.1 ± 12.4 kg, BCS: 3.0 ± 0.2) or hCG (n = 27; BW: 45.8 ± 14.2 kg, BCS: 3.0 ± 0.4). After MAP sponge removal, goats in estrus were either artificially inseminated (n = 22), in a standing position [18], at 22-24 h after the onset of estrus or naturally mated (n = 52) by fertile bucks at the onset of behavioral estrus and then every 12 h throughout estrus. AI utilized commercial frozen/thawed semen with a minimum of 45% progressive motility and 3 spermatic vigor (0-5 variation) from four bucks (two Saanen and two Alpine) aged 2-4 years, participating in the Brazilian progeny test -CapraGene (donated by Embrapa Goats and Sheep).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Experiment 2, eighty multiparous dairy goats with at least seven months of lactation (15 Alpine, 38 Saanen and 27 Toggenburg) were grouped by milk production, breed, BW, BCS and breeding methods, and then similarly allocated to one of the following gonadotropin treatments: pFSH (n = 26; BW: 45.1 ± 14.9 kg, BCS: 3.0 ± 0.4), eCG (n = 27; BW: 45.1 ± 12.4 kg, BCS: 3.0 ± 0.2) or hCG (n = 27; BW: 45.8 ± 14.2 kg, BCS: 3.0 ± 0.4). After MAP sponge removal, goats in estrus were either artificially inseminated (n = 22), in a standing position [18], at 22-24 h after the onset of estrus or naturally mated (n = 52) by fertile bucks at the onset of behavioral estrus and then every 12 h throughout estrus. AI utilized commercial frozen/thawed semen with a minimum of 45% progressive motility and 3 spermatic vigor (0-5 variation) from four bucks (two Saanen and two Alpine) aged 2-4 years, participating in the Brazilian progeny test -CapraGene (donated by Embrapa Goats and Sheep).…”
Section: Methodsmentioning
confidence: 99%
“…Evolution of cervical mucus can be performed when the cervical os is observed with the speculum inserted into the vagina, as described earlier [18]. The evaluation of mucus present in the vulva can also be accomplished.…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial insemination using chilled and frozen semen can accelerate animal production in breeder farms, simultaneously increasing genetic progress. Indeed, numerous studies have already demonstrated the efficiency of artificial insemination in small ruminants [4][5][6][7][8][9][10][11]. In a comparative study between extenders for freezing semen, a pregnancy rate of 54.55-63.64% was found in Rhamani ram [4], a lambing rate of 56.7-64.5% in Suffolk ewes [5], and a pregnancy rate of 46.2-71% of in Chios rams [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a comparative study between extenders for freezing semen, a pregnancy rate of 54.55-63.64% was found in Rhamani ram [4], a lambing rate of 56.7-64.5% in Suffolk ewes [5], and a pregnancy rate of 46.2-71% of in Chios rams [6]. In goats, depending on the insemination protocol, fertility varied from 30.3% to 52.5% [7], 38-50% according to the frozen semen type used [8], 35-65% by the synchronization method used [9], 62-64.3% depending on the number of inseminations done [10], and 46-75% per time taken to inseminate a goat [11]. Most of the semen used is frozen in extenders containing animal substances such Available at www.veterinaryworld.org/Vol.14/June-2021/2.pdf as lecithin protein [8,12], increasing the risk of the spread of animal diseases.…”
Section: Introductionmentioning
confidence: 99%